Complex 3D Migration and Delayed Triggering of Hydraulic Fracturing‐Induced Seismicity: A Case Study Near Fox Creek, Alberta. Issue 2 (18th January 2022) - Gao, Dawei; Kao, Honn; Wang, Bei; Visser, Ryan; Schultz, Ryan; Harrington, Rebecca M.
Abstract: Earthquakes resulting from hydraulic fracturing (HF) can have delayed triggering relative to injection commencement over a varied range of time scales, with the majority of M ≥ 4 mainshocks occurring near/after well completion. This poses serious challenges for risk mitigation and hazard assessment. Here, we document a high‐resolution, three‐dimensional source migration process with delayed mainshock triggering that is controlled by local hydrogeological conditions near Fox Creek, Alberta, Canada. Our results reveal that poroelastic effects might contribute to induced seismicity, but are probably insufficient to activate a large fault segment not critically stressed. The rapid pore‐pressure build‐up from HF can be very localized and capable of producing large, felt earthquakes if adequate hydrological paths exist. We interpret the delayed triggering as a manifestation of pore‐pressure build‐up along pre‐existing faults needed to facilitate seismic failure. Our findings can explain why so few injection operations are seismogenic. Plain Language Summary: Fluid injection‐induced earthquakes (IIE), especially those M ≥ 4 mainshocks, are often observed to occur near or after well completion. Such delayed triggering relative to injection commencement poses serious challenges for both regulators and the energy industry to establish an effective mitigation strategy for the potential seismic risk. In this study, we reveal a high‐resolution, complex three‐dimensional pattern of IIE migration near Fox Creek, Alberta, Canada. The observed first‐outward‐then‐inward IIE sequence highlights the significance of hydrogeological networks in facilitating fluid pressure migration and the associated seismic failure. The detailed spatiotemporal distribution of IIE suggests that the effect of pore‐pressure build‐up from hydraulic fracturing (HF) can be very localized. The delayed triggering is a combined result of the fluid pressure migration and the current stress state of the hosting fault system away from the HF wells. The findings from this study also provide plausible explanations on why only a very limited number of fluid injections are seismogenic. Key Points: We document a complex 3D source migration process with delayed mainshock triggering that is controlled by a local hydrogeological setting Poroelastic effects contribute to induced events but are probably insufficient to activate a large fault segment not critically stressed Rapid pore‐pressure build‐up can be very localized and lead to large earthquakes if adequate hydrological paths exist